State, Sovereignty, War : Civil Violence in Emerging Global Realities. - Kapferer, Bruce (Critical Interventions: A Forum for Social Analysis., 2013)
The very institution of the state is widely conceived of as inseparable from war. If it constitutes peace within the borders or order of its sovereignty, this very peace may be the condition for its potential for war with those other states and social formation outside it. This volume represents different analytical standpoints and positions within global processes, inviting further discussion on contemporary realities and the development of new formations of war and violence.